A Novel Heptapeptide, GPPGPAG Transfers to the Brain, and Ameliorates Memory Dysfunction and Dendritic Atrophy in Alzheimer’s Disease Model Mice - Tohda, Chihiro; Kogure, Chisato; Nomoto, Kaori; Toledo, Andreia de; Yang, Ximeng; Hirano, Eiichi (Frontiers in Pharmacology, 2021)
We investigate the effects of a heptapeptide, GPPGPAG, on memory improvement and neuritic regeneration in Alzheimer’s disease models and evaluate it as a new anti-Alzheimer’s disease (AD) therapy. The anti-AD effects of GPPGPAG were evaluated in Aβ-treated cortical neurons and 5XFAD, a mouse model of AD. Exposure of cortical neurons to Aβ25-35 for 3 days resulted in atrophy of axons and dendrites. Treatment with GPPGPA improved the dendritic atrophy of Aβ-treated cortical neurons, but not axonal atrophy. Postsynaptic and presynaptic densities under Aβ1-42 exposure were increased by GPPGPAG treatment. Oral administration of GPPGPAG to 5XFAD mice for 15 days showed significant improvement in object recognition memory and dendritic density. Direct infusion of GPPGPAG into the lateral ventricle of 5XFAD mice for 28 days improved object recognition memory. Following oral administration of GPPGPAG in mice, the undigested heptapeptide was detected in the plasma and cerebral cortex. Analysis of target protein of GPPGPAG in neurons by DARTS method identified 14-3-3ε binding. The protective effect of GPPGPAG on Aβ1-42-induced dendritic atrophy was cancelled by knockdown of 14-3-3ε. Together, these results suggest that GPPGPAG is orally available, transfers to the brain, and ameliorates memory dysfunction in AD brain, possibly by 14-3-3ε mediated dendritic restoration.